Phylogenetic Distribution of Polysaccharide-Degrading Enzymes in Marine Bacteria - Sun, Zhong-Zhi; Ji, Bo-Wen; Zheng, Ning; Wang, Meng; Cao, Ye; Wan, Lu; Li, Yi-Song; Rong, Jin-Cheng; He, Hai-Lun; Chen, Xiu-Lan; Zhang, Yu-Zhong; Xie, Bin-Bin (Frontiers in Microbiology, 2021)
Deconstruction is an essential step of conversion of polysaccharides and polysaccharide-degrading enzymes play key roles in this process. Though recent progress in the identification of these enzymes, the diversity and phylogenetic distribution of these enzymes in marine microorganisms remain largely unknown, hindering our understanding of the ecological roles of marine microorganisms in the ocean carbon cycle. Here, we studied the phylogenetic distribution of nine types of polysaccharide-degrading enzymes in marine bacterial genomes. Firstly, we manually compiled a reference sequence database containing 961 experimentally verified enzymes. With this reference database, we annotated 9,335 enzyme sequences from 2,182 high-quality marine bacterial genomes, revealing extended distribution for six enzymes at the phylum level and for all nine enzymes at lower taxonomic levels. Next, phylogenetic analyses revealed intra-clade diversity in the encoding potentials and phylogenetic conservation of a few enzymes at the genus level. Lastly, our analyses revealed correlations between enzymes, with alginate lyases demonstrating the most extensive correlations with others. Intriguingly, chitinases showed negative correlations with cellulases, alginate lyases, and agarases in a few genera, respectively. This result suggested that intra-genus lifestyle differentiation occurred many times in marine bacteria and that the utilization of polysaccharides may act as an important driver in the recent ecological differentiation of a few lineages. This study expanded our knowledge of the phylogenetic distribution of polysaccharide enzymes and provided insights into the ecological differentiation of marine bacteria.